Functional expression of the leftward open reading frames of the A component of tomato golden mosaic virus in transgenic tobacco plants. - Hanley-Bowdoin, L (1989)
The genome of the geminivirus tomato golden mosaic virus (TGMV) consists of two circular DNA molecules designated as components A and B. We have constructed Nicotiana benthamiana plants that are transgenic for the three overlapping open reading frames, AL1, AL2, and AL3, from the left side of TGMV A. In the transgenic plants, the AL open reading frames are under the control of the cauliflower mosaic virus (CaMV) 35S promoter. In TGMV infectivity assays, seven of 10 transgenic lines complemented TGMV A variants with mutations in AL1, AL2, or AL3 when co-inoculated with the B component. The 35S-AL construct was transcribed as a single RNA species in the transgenic plants, indicating that AL1, AL2, and AL3 were expressed from a polycistronic mRNA. This differs from the complex transcription pattern in TGMV-infected plants, which contains five AL transcripts. There was no quantitative correlation between the efficiency of complementation in the infectivity assay and the level of expression of transgenic AL RNA in the leaves of a transgenic line. One line that failed to complement defects in AL1, AL2, and AL3 in infectivity assays contained high levels of transgenic AL RNA and functional AL1 protein. These results provide evidence that chromosomal position can affect the cell- and tissue-specific transcription of the 35S promoter in transgenic plants. Comparison of the complementing plants and wild-type infected plants may provide insight into the TGMV infection process and the use of the CaMV 35S promoter for gene expression in transgenic plants.